A genre analysis on the introductory sections of empirical research articles written by non-native english speakers publishing in Malaysian journals - Lim,, Swee Hoon. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to examine the textual organization and language features found in research articles (RA) Introduction section of empirical studies in Applied Linguistics (AL) written by NNES publishing in Malaysian journals. The objectives are to identify the extent to which NNES research article‟s introduction sections employ a similar structure to the Swales‟ (2004) revised Create-A-Research-Space (CARS) model and the extent to which the language features (e.g. tenses, lexical signals) contained within key moves/obligatory steps of the Introduction section are similar to the language features proposed by Swales and Feak (2004). A total of 50 introductory sections of empirical AL RAs written by NNES in 7 Malaysian Online Journals were selected according to pre-determined criteria. Results of analysis showed that most of the NNES writers were aware and complied with the CARS model in terms of having all 3 obligatory moves in their introductory sections (35 out of 50). However, there was a marked divergence from the ordering of the moves where most did not follow M1- M2-M3 (CARS model) in a single path. Here, 34% applied the M1-M3-[other moves] flow while 52% showed skeletal signs of M1-M2-M3 interspersed with the reoccurrence of the moves. It was also noted that M1S3 (reviewing items of previous literature) exhibit the highest average occurrence per section and in terms of M2 (Establishing niche), M2S2 (Providing positive justification) was a more popular step than indicating gaps. For language features results, there was higher compliance to the checklist where the writers employed language items proposed. Furthermore, there was a prominent usage of modal auxiliaries especially in M1S3 to indicate tentativeness or make suggestions/proposals which was not described in the checklist. As a whole, the writers were seen to be able to convey the function of moves/steps effectively using language features proposed but the glitch lies in structuring the information in the introductory section.